PERENCANAAN SISTEM OPTICAL TRANSPORT NETWORK (OTN) PADA SISTEM TRANSMISI DWDM - Maeli Khusnul Munfiqoh; Repdhi Febriyan; Lubna Nadra Hasti; Muhammad Rofiq; Didik Aribowo (International Forum of Researchers and Lecturers, 2023)
An OTN consists of a set of optical network elements connected by a fiber-optic link. OTN can provide the use of transport, multiplexing, routing, management, supervision and resilience of optical channels. OTN (Optical Transport Network) itself is a technology that can increase network bandwidth and reliability by building network functions into optical networks. . An OTN consists of a set of optical network elements connected by a fiber-optic link.